2013
DOI: 10.1002/pro.2395
|View full text |Cite
|
Sign up to set email alerts
|

Solution properties of γ‐crystallins: Compact structure and low frictional ratio are conserved properties of diverse γ‐crystallins

Abstract: c-crystallins are highly specialized proteins of the vertebrate eye lens where they survive without turnover under high molecular crowding while maintaining transparency. They share a tightly folded structural template but there are striking differences among species. Their amino acid compositions are unusual. Even in mammals, c-crystallins have high contents of sulfurcontaining methionine and cysteine, but this reaches extremes in fish cM-crystallins with up to 15% Met. In addition, fish cM-crystallins do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
(129 reference statements)
3
23
0
Order By: Relevance
“…suited for their role in the lens. The intramolecular packing involving the coming together of the N-terminal and C-terminal domains generates a compact monomeric globule of about 5 nm in size, i.e., Stokes radius of 2.13 nm [9], and a low frictional ratio of about 1.21 (only slightly above the value of 1.12 for a perfect compact smooth protein sphere), suggesting that they have low hydration and a low propensity for sticky interactions with solvent and perhaps, with other proteins [10]. These small globules, packed at such high concentrations in the lens (400-1000 mg/ml), are seen to exhibit short range order which is necessary for transparency, particularly in a crowded macromolecular environment as in the lens [11].…”
Section: Section I: Thementioning
confidence: 99%
“…suited for their role in the lens. The intramolecular packing involving the coming together of the N-terminal and C-terminal domains generates a compact monomeric globule of about 5 nm in size, i.e., Stokes radius of 2.13 nm [9], and a low frictional ratio of about 1.21 (only slightly above the value of 1.12 for a perfect compact smooth protein sphere), suggesting that they have low hydration and a low propensity for sticky interactions with solvent and perhaps, with other proteins [10]. These small globules, packed at such high concentrations in the lens (400-1000 mg/ml), are seen to exhibit short range order which is necessary for transparency, particularly in a crowded macromolecular environment as in the lens [11].…”
Section: Section I: Thementioning
confidence: 99%
“…These four tryptophans are conserved in all human lens βγ-crystallin domains except for the quenching tryptophan in the second domain of βB2 and βA2, while in fish γM-crystallins, the pair can be absent from one or both domains (Chen et al, 2013; Zhao et al, 2013). The Ciona calcium-bound domain has both corner and quenching tryptophans, suggesting that the pair may have an ancestral function, while in βγ-domains within AIM1 and CRYBG3, the quenching tryptophan is only moderately conserved, and it is absent in the sponge domains.…”
Section: : Structure Of β- and γ-Crystallinsmentioning
confidence: 99%
“…In solution, all γ-crystallins exhibit low frictional ratios and partial specific volumes compared with other proteins (Chen et al, 2013). A survey of the amino acid composition of all proteins found that γ-crystallins have unusually high contents of residues with higher refractive index increments which may make a significant contribution to increased refractive power of the lens (Zhao et al, 2011).…”
Section: : Structure Of β- and γ-Crystallinsmentioning
confidence: 99%
See 2 more Smart Citations